Composition of the alfalfa pathobiome in commercial fields - Nemchinov, Lev G.; Irish, Brian M.; Uschapovsky, Igor V.; Grinstead, Sam; Shao, Jonathan; Postnikova, Olga A. (Frontiers in Microbiology, 2023)
Through the recent advances of modern high-throughput sequencing technologies, the "one microbeone disease" dogma is being gradually replaced with the principle of "pathobiome". Pathobiome is a comprehensive biotic environment that not only includes a diverse community of all disease-causing organisms within the plant, but also defines their mutual interactions and resultant effect on plant health. To date, the concept of pathobiome as a major component in plant health and sustainable production of alfalfa (Medicago sativa L.), the most extensively cultivated forage legume in the world, is non-existent. Here we approached this subject by characterizing the biodiversity of alfalfa pathobiome using high throughput sequencing technology. Our metagenomic study revealed a remarkable abundance of different pathogenic communities associated with alfalfa in the natural ecosystem. Profiling of the alfalfa pathobiome is a starting point to assess known and identify new and emerging stress challenges in the context of plant disease management. In addition, it allows to address the complexity of microbial interactions within the plant host and their impact on the development and evolution of pathogenesis.